IMPLEMENTATION OF EXPERT SYSTEM TO IDENTIFY FORMALIN AND BORAX CONTENT IN FOOD USING THE CERTAINTY FACTOR METHOD - Lisa Pristiwani Hasibuan; Volvo Sihombing; Muhammad Halmi Dar (Sean Institute, 2021)
Today, along with the times that are supported by the rapid development of technology, all aspects of life cannot be separated from the influence of technology. In terms of food, it is also supported by the role of women, nowadays women are born not only to take care of the household, but also to become women who earn big or often called career women, so that there is almost no time to prepare food for the family, so it is not surprising that food Fast food is preferred as one of the main alternatives to filling the stomach considering the taste of the food served and the serving time is only a matter of minutes so it doesn't waste a lot of time. However, without realizing it, some types of fast food that are often consumed contain several types of harmful ingredients that trigger the onset of chronic diseases, such as: heart attack, insulin resistance, diabetes, and several other dangerous diseases. Seeing this impact, so the author is interested in making an expert system application to identify the content of formalin and borax in food. In drawing conclusions in expert systems, Forward Chaining and Backward Chaining are generally used. However, with the use of these two reasons, it is not possible to determine the value of confidence in the hypothesis. So that the expert system can do reasoning like an expert even in conditions of data uncertainty and to get a confidence value in this case the author uses a method to solve the data using the Certainty Factor (CF) method. The Certainty Factor method is a method that defines a measure of certainty against a fact or rule, to describe the level of expert confidence in the problem at hand,